Exploring the Interplay: Social Media Use and Social Anxiety Among Millennials in the Digital Age - Muhammad Bayu; Sri Rahayu Puti (PELNUS | Pen en Light for Natural Union of Science, 2023)
This research embarks on an exploration of the intricate relationship between social media use and social anxiety within the millennial generation. Grounded in the context of the digital age, our study aims to unravel the complexities, nuances, and implications of this dynamic interplay. Employing a cross-sectional design, a diverse sample of millennials participated in surveys that probed their social media habits, experiences, and levels of social anxiety. The findings of our research reveal a significant positive correlation between the frequency and duration of social media use and heightened levels of social anxiety among millennials. This confirmation aligns with existing literature, emphasizing the robustness of the observed relationship. Furthermore, the study introduces novel dimensions, elucidating platform-specific nuances, the mediating role of Fear of Missing Out (FOMO), gender dynamics, and temporal adaptations in the correlation. Implications drawn from these findings offer valuable insights for mental health interventions, societal reflections, and future research endeavors. Tailored strategies addressing the unique stressors associated with digital engagement are crucial, considering the identified correlation. Platform-specific awareness and education become imperative for empowering individuals to make informed choices about their digital interactions.